Argentina betrayed : memory, mourning, and accountability - Robben, Antonius C. G. M. (Pennsylvania studies in human rights., 2018)
This riveting analysis of the aftermath of Argentina's massive disappearances uncovers a dynamic of trust and betrayal that has driven relentless confrontations between the state, the military, former insurgents, and bereaved relatives about how to remember, mourn, and punish atrocities committed against fellow citizens.